2010
DOI: 10.1152/physiolgenomics.00038.2010
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin (5-HT) receptor 5A sequence variants affect human plasma triglyceride levels

Abstract: Neurotransmitters such as serotonin (5-hydroxytryptamine, 5-HT) work closely with leptin and insulin to fine-tune the metabolic and neuroendocrine responses to dietary intake. Losing the sensitivity to excess food intake can lead to obesity, diabetes, and a multitude of behavioral disorders. It is largely unclear how different serotonin receptor subtypes respond to and integrate metabolic signals and which genetic variations in these receptor genes lead to individual differences in susceptibility to metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…First, although the common postulation indicates that lower TC levels, particularly LDL-C levels, lead to reduced central serotonin activity by changing the expression of the 5-HT-2 receptors (Golomb, 1998;Golomb et al, 2000;Kaplan et al, 1997), a recent study found that 5-HT-5A receptors may also regulate plasma TG levels (Zhang et al, 2010). Thus, lower levels in many lipid indexes, including TC, LDL-C, and TG, might be associated with more violence via reduced central serotonin activity modulated through different types of serotonin receptors.…”
Section: Discussionmentioning
confidence: 99%
“…First, although the common postulation indicates that lower TC levels, particularly LDL-C levels, lead to reduced central serotonin activity by changing the expression of the 5-HT-2 receptors (Golomb, 1998;Golomb et al, 2000;Kaplan et al, 1997), a recent study found that 5-HT-5A receptors may also regulate plasma TG levels (Zhang et al, 2010). Thus, lower levels in many lipid indexes, including TC, LDL-C, and TG, might be associated with more violence via reduced central serotonin activity modulated through different types of serotonin receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our research team had not considered rs39179 (minor allele frequency 2.6% in our cohort; present in 25 of the 258 families and explained 0.7% of the variation in triglycerides) a promising candidate and rather focused on other SNPs. 17,18 Our results suggest that either rs39179 or SNPs in strong linkage disequilibrium (LD) with rs39179 may be causal. Using SNAP, 36 a single ungenotyped SNP (rs10276884) in strong LD with rs39179 was identified.…”
Section: Discussionmentioning
confidence: 82%
“…16 Although this region has been densely genotyped, MGA yielded associations that explained little of the observed linkage. 17,18 Using VIOLET, a single SNP (rs39179) accounting for 24% of the LOD score was identified (but it did not reach the traditional CLA threshold). This SNP was only nominally associated in MGA (P ¼ 0.04) and was ranked eighty-ninth in the P-value ranking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations